(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Motivation and self-efficacy play crucial roles in achieving goals and determining one’s capability to succeed. This study explored the relationship between motivation and self-efficacy through a descriptive-correlational approach, and 260 participants were selected using proportionate stratified random sampling from an institution in the Philippines. The Motivated Strategies for Learning Questionnaire was utilized to assess participants’ motivation levels, while the Java Programming Self-Efficacy Scale measured their self-efficacy in Java Programming. Data analysis based on sex, chronological age, and year level revealed no significant differences in motivation, except for variations in course. Self-efficacy levels did not exhibit notable distinctions related to sex, chronological age, and course. However, a statistically significant difference was observed across different year levels. The findings demonstrated a significant correlation between motivation and self-efficacy. Most participants exhibited high motivation levels indicating better academic performance; however, their high test anxiety insinuated more worrying during the examination. First-year students had lower self-efficacy in Java Programming than higher years, implying that self-efficacy tends to improve as the year level advances. This study highlights the importance of addressing students’ difficulties and underperformance in Java Programming and preparing them to navigate complex and intimidating situations within the program. By enhancing self-efficacy and maintaining motivation, students can better adapt to new challenges and succeed in their academic pursuits.